Multivariate analysis of the effects of age, particle size and landfill depth on heavy metals pollution content of closed and active landfill precursors. (August 2018) - Adelopo, A.O.; Haris, P.I.; Alo, B.I.; Huddersman, K.; Jenkins, R.O.
Highlights: Landfill precursors were analyzed for toxic heavy metals using ICP-MS. Heavy metals pollution indices and potential human health risk factor determined. Relationship determined using Cluster and Principal component analysis (PCA) Pollution potential of these metals during reuse were discussed. Abstract: Multivariate analysis of a heavy metal pollution survey of closed and active landfill precursors was carried out in order to compare environmental risk levels in relation to age, particle size and depth of the precursors. Landfill precursors (77) were collected and analyzed for 15 USEPA toxic heavy metals using ICP-MS. Heavy metals concentrations in closed landfill precursors were significantly higher than those in the active landfill for 11 of 15 heavy metals investigated (closed landfill order: Fe > Al > Mn > Cu > Pb > Ba > Co > Cr > Ni > Cd > As > Se > Ti). Cluster analysis and correlation studies indicated the distribution of the metals was more influenced by landfill precursor size than by depth of the sample. Principal component analysis (PCA) showed that 10 of 15 of heavy metals of both landfill precursors were from similar anthropogenic sources. Heavy metals pollution indices (Igeo  > 5, EF > 40 and CF > 7) of both active and closed landfill precursors exceeded limits in the order of Zn > Cd > Pb > Cu > Ag, indicating a major potential health risk influenced by age and particle size of precursor. Zn, Cd, Cu and Pb of both landfill precursors exceeded the USEPA set standard for assessment of human health risk for each of the metals (1 × 10 −4 to 1 × 10 −3 ). This study highlights the need for the integration of a clean-up process for precursors from both types of landfill to reduce possible environmental pollution during a reuse process.